A Justification of Two-Dimensional Nonlinear Viscoelastic Shells Model. (19th February 2012) - Li, Fushan
Abstract : By applying formal asymptotic analysis and Laplace transformation, we obtain two-dimensional nonlinear viscoelastic shells model satisfied by the leading term of asymptotic expansion of the solution to the three-dimensional equations.